Gigi Tiruan Sebagian Kerangka Logam sebagai Penunjang Kesehatan Jaringan Periodontal - Putri Lenggogeny; Sri Lelyati C Masulili (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Frame Partial Denture as a Supportive Therapy for Periodontal Health. Partial denture is very important in maintaining periodontal health and maintaining the stability of the remaining teeth. The fabrication of denture is an important phase in comprehensive periodontal health therapy, so as to maintain the periodontal health. Removable partial dentures should be designed to reduce the accumulation of food residue and plaque on the teeth and gingival edge of the abutment. The selection of metallic materials as denture in case of periodontal compromise can help in preventing tooth movement and maintain the position of the teeth after periodontal treatment because the nature of metal is more rigid when compared with other materials, so that the success of the treatment can be achieved. Making good metal framework denture and good cooperation between all members of the medical team in handling the case will result in a successful treatment. The aim of the study is to enrich the knowledge for periodontists and prosthodontists in using metal removable prothesis in compromised periodontal patients. Providing information and educating patients in maintaining the cleanliness of denture and mouth are also an important factor that determines the success of the manufacture of dentures.